2019
DOI: 10.1111/jcmm.14394
|View full text |Cite
|
Sign up to set email alerts
|

Wnt3a promotes radioresistance via autophagy in squamous cell carcinoma of the head and neck

Abstract: The canonical Wnt/β‐catenin signalling pathway and autophagy play critical roles in cancer progression. However, the role of Wnt‐mediated autophagy in cancer radioresistance remains unclear. In this study, we found that irradiation activated the Wnt/β‐catenin and autophagic signalling pathways in squamous cell carcinoma of the head and neck (SCCHN). Wnt3a is a classical ligand that activated the Wnt/β‐catenin signalling pathway, induced autophagy and decreased the sensitivity of SCCHN to irradiation both in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…The Wnt/b-catenin signalling is a highly evolutionary conserved pathway that is implicated in many vital biological processes, such as embryonic development, stem cell regeneration, tissue homeostasis and cell survival [18][19][20]. Studies have shown Wnt/b-catenin signalling is often upregulated in a variety of cancer, which endows cells with a stem-like phenotype that enhances self-renewal ability, multi-differential potential, and induces epithelial-to-mesenchymal transition of cancer cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/b-catenin signalling is a highly evolutionary conserved pathway that is implicated in many vital biological processes, such as embryonic development, stem cell regeneration, tissue homeostasis and cell survival [18][19][20]. Studies have shown Wnt/b-catenin signalling is often upregulated in a variety of cancer, which endows cells with a stem-like phenotype that enhances self-renewal ability, multi-differential potential, and induces epithelial-to-mesenchymal transition of cancer cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The activated Wnt signaling pathway exerts critical functions in malignant cancer progression, including the emergence of radioresistance. 30 Among Wnt ligands, there are more than 19 closely related but distinct secreted cysteine-rich glycoproteins. The basic expression level of β-catenin is associated with a favorable or unfavorable prognosis in several solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma of head and neck cell colonies were stained 2 weeks later and counted by Image J v1.8.0 (positive colony was defined as >50 cells) …”
Section: Methodsmentioning
confidence: 99%
“…The western blot assay was carried out according to our previous studies . Antibody information is listed in Table .…”
Section: Methodsmentioning
confidence: 99%